Colony stimulating factor 1 receptor inhibition eliminates microglia and attenuates brain injury after intracerebral hemorrhage - Li, Minshu (J Cereb Blood Flow Metab, 2016)
Microglia are the first responders to intracerebral hemorrhage, but their precise role in intracerebral hemorrhage remains to be defined. Microglia are the only type of brain cells expressing the colony-stimulating factor 1 receptor, a key regulator for myeloid lineage cells. Here, we determined the effects of a colony-stimulating factor 1 receptor inhibitor (PLX3397) on microglia and the outcome in the context of experimental mouse intracerebral hemorrhage. We show that PLX3397 effectively depleted microglia, and the depletion of microglia was sustained after intracerebral hemorrhage. Importantly, colony-stimulating factor 1 receptor inhibition attenuated neurodeficits and brain edema in two experimental models of intracerebral hemorrhage induced by injection of collagenase or autologous blood. The benefit of colony-stimulating factor 1 receptor inhibition was associated with reduced leukocyte infiltration in the brain and improved blood–brain barrier integrity after intracerebral hemorrhage, and each observation was independent of lesion size or hematoma volume. These results demonstrate that suppression of colony-stimulating factor 1 receptor signaling ablates microglia and confers protection after intracerebral hemorrhage.